TINJAUAN LOYALITAS NASABAH BERDASARKAN KUALITAS LAYANAN DAN KEPUASAN PADA BCA FATMAWATI - Salwa Putri Purwitasari, (2023)
Banks play a crucial role in supporting economic activities, and good service quality can have a positive impact on customer loyalty. Loyalty can be influenced by service quality and customer satisfaction. Bank Central Asia (BCA) continuously evolves to adapt to the current era. Qualitative writing is a type of writing used to understand social life, which is obtained and analyzed using a qualitative (non-quantitative) approach. SmartPLS has the advantage of a strong analytical method, allowing for the processing of a small number of samples. Good service quality that aligns with customer needs can enhance customer satisfaction and increase loyalty.